The relationship between cultural dimensions and goal orientation - Nogueira, Madalena Maltês de Almeida (2018)
The purpose of this study consists on understanding the relationship between cultural dimensions and goal orientation. Specifically, the research seeks to explore if some cultural dimensions of GLOBE Project are related to goal orientation, specifically Learning and Performance Goal Orientation. A quantitative research method was used in the study to collect responses from individuals through an online survey previously elaborated. The relationship between five cultural dimensions and Learning and Performance Goal Orientation were tested through multiple linear regressions to understand if there were significant relationships between them and to test if those were positive or negative. The results supported two out of five hypotheses proposed. Performance Orientation was positively related to Learning Goal Orientation, as well as Institutional Collectivism was negatively related to Performance Goal Orientation. Although the opposite relationship was proposed in the hypothesis, the relationship between High Power Distance and Performance Goal Orientation was significant. Remaining relationships tested did not yield significant findings. Finally, the results obtained could provide important information about specific cultural behaviors needed to engage with to incur and follow a particular goal orientation, as well as, significant information to future research in this area.